2007
DOI: 10.1007/s00422-007-0200-2
|View full text |Cite
|
Sign up to set email alerts
|

Parametric spectral analysis of nonstationary fluctuations of excitatory synaptic currents

Abstract: We assessed on Monte-Carlo simulated excitatory post-synaptic currents the ability of autoregressive (AR)-model fitting to evaluate their fluctuations. AR-model fitting consists of a linear filter describing the process that generates the fluctuations when driven with a white noise. Its fluctuations provide a filtered version of the signal and have a spectral density depending on the properties of the linear filter. When the spectra of the non-stationary fluctuations of excitatory post-synaptic currents were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The main motivation for choosing second order model was that it provides more control over the estimated parameters (eg., phase) than higher order AR processes. Additionally, in this paper [12] the authors have shown with second order AR processes the phase estimation for narrow band frequency spectrum is optimal than higher order AR processes. In our case the phase estimation was based on a single peak frequency and not on a broad band frequency spectrum.…”
Section: Auto-regressive Process and Phase Differencementioning
confidence: 81%
See 1 more Smart Citation
“…The main motivation for choosing second order model was that it provides more control over the estimated parameters (eg., phase) than higher order AR processes. Additionally, in this paper [12] the authors have shown with second order AR processes the phase estimation for narrow band frequency spectrum is optimal than higher order AR processes. In our case the phase estimation was based on a single peak frequency and not on a broad band frequency spectrum.…”
Section: Auto-regressive Process and Phase Differencementioning
confidence: 81%
“…However, before utilizing any of these approaches, the forward problem must be solved. The solution is based on either spherical head models (single sphere [11] and concentric spheres [12]) or realistic head models (boundary element method (BEM) [13] and finite element method (FEM) [14]). After developing any new method, the best way to test its robustness is to apply the simulation to a dataset in which the results are already known.…”
Section: Introduction Eeg (Electroencephalogrammentioning
confidence: 99%